Acid-Stable Cu Cluster Precatalysts Enable High Energy and Carbon Efficiency in CO2 Electroreduction - Kim, Dongha; Park, Sungjin; Lee, Junwoo; Chen, Yiqing; Li, Feng; Kim, Jiheon; Bai, Yang; Huang, Jianan Erick; Liu, Shijie; Jung, Eui Dae; Lee, Byoung Hoon; Papangelakis, Panagiotis; et al. (Journal of the American Chemical Society, 2024)
The electrochemical reduction of CO2 in acidic media offers the advantage of high carbon utilization, but achieving high selectivity to C2+ products at a low overpotential remains a challenge. We identified the chemical instability of oxide-derived Cu catalysts as a reason that advances in neutral/alkaline electrolysis do not translate to acidic conditions. In acid, Cu ions leach from Cu oxides, leading to the deactivation of the C2+-active sites of Cu nanoparticles. This prompted us to design acid-stable Cu cluster precatalysts that are reduced in situ to active Cu nanoparticles in strong acid. Operando Raman and X-ray spectroscopy indicated that the bonding between the Cu cluster precatalyst ligand and in situ formed Cu nanoparticles preserves a high density of undercoordinated Cu sites, resulting in a C2H4 Faradaic efficiency of 62% at a low overpotential. The result is a 1.4-fold increase in energy efficiency compared with previous acidic CO2-to-C2+ electrocatalytic systems.
Keywords: Acidic media; Carbon efficiency; Carbon utilization; Cu nano-particles; Electro reduction; Electrochemical reductions; High carbons; High energy efficiency; Overpotential; Precatalysts